Formulasi Sediaan Salep Dari Ekstrak Daun Katuk (Sauropus androgynus (L.) Merr.) - Lidyawati Lidyawati; Nurul Hidayati; Ria Ceriana (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Katuk (Sauropus androgynus (L.) Merr.) is a plant that has secondary metabolic compounds with various potentials and contains several chemical compounds, including papaverine alkaloids, proteins, fats, vitamins, minerals, saponins, flavonoids and tannins. Katuk leaves can work as antioxidants because they contain phenolic compounds, namely flavonoids. The potential of katuk leaves is also supported by research on pharmacological activities as antibacterial, antihypertensive, antihyperlipidemic, anti-infective, anti-inflammatory, antianemic and increasing milk production. The purpose of this study was to determine whether katuk leaves can be formulated in the form of an ointment. Ointment is defined as a semi-solid preparation that is easily applied and used as an external drug. Ointment is also one of the dosage forms with a semisolid consistency that is oily and generally does not contain water and contains the active ingredient dissolved or dispersed in a vehicle. This study used 4 treatments with various concentrations, namely FO: control formulation of ointment base, FI: formulation of katuk leaf extract ointment preparation with 10% concentration, FII: formulation of katuk leaf extract ointment preparation with 15% concentration, FIII: formulation of katuk leaf extract ointment preparation with a concentration of 20%. Evaluation of the ointment using organoleptic tests, homogeneity, pH, spreadability, stability and irritation. The results of the evaluation carried out on the ointment preparation were stable and did not irritate the skin.